Cymbidium ×shangrilaense (Orchidaceae; Epidendroideae), a new natural hybrid from China: evidence from morphology and molecular analyses - Ke, Shijie; Zhu, Meng-Jia; Zhao, Xuewei; Liu, Ding-Kun; Li, Yuanyuan; Huang, Jie; Zhang, Qing-Hai; Liu, Zhong-Jian; Lan, Siren (Phytotaxa, 2022)
A new natural hybrid of Cymbidium (Orchidaceae), C. ×shangrilaense, from Yunnan Province, China, is illustrated and described. This entity may be a natural hybrid between C. tracyanum and C. gaoligongense. Morphologically, it differs from former by epidermal stripes and column and lip midlobe morphology and from the latter by its flower veins and lip morphology. Molecular analysis based on nuclear (ITS) DNA clearly indicated a relationship of the natural hybrid to group of Cymbidium species, whereas the plastid DNA (matK and rbcL) tree confirmed the natural hybrid as sister to C. tracyanum, C. subgenus Cyperorchis.